PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP PENGELUARAN ZAKAT PADA BANK UMUM SYARIAH DI INDONESIA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (2011-2020) - Siti Fatimatuzzahro (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2022)
Abstract This study aims to analyze the effect of profitability and liquidity on zakat expenditure with company size as a moderating variable. The technique used in selecting the sample is purposive sampling. The samples selected in this study amounted to 7 of 14 Islamic Commercial Banks in Indonesia for the 2011-2020 period. The data collection technique in this study uses the documentation method by searching for data by visiting the official website of Islamic Commercial Banks. Simultaneously, this study shows the results of the profitability variable (ROA) and the liquidity variable (FDR) have a significant positive effect on zakat expenditure on BUS. While partially the results obtained are the profitability variable (ROA) has a significant negative effect, while the liquidity variable (FDR) has no significant positive effect, this study also shows the results that company size as measured by total assets in this study is able to moderate profitability (ROA). but is unable to moderate the relationship between liquidity (FDR) and zakat expenditures at Islamic Commercial Banks.